PENGAJARAN DAN PEMBELAJARAN SUBJEK SEJARAH PRAUNIVERSITI. - BANGGU, JAITUN; KIFLEE@DZULKIFLI, DG. NORIZAH AG. (MANU: Jurnal Pusat Penataran Ilmu dan Bahasa (PPIB), 2026)
This study explores the implementation of teaching and learning practices in preuniversity History by examining the pedagogical strategies employed by teachers and the factors that support effective classroom practice. A qualitative case study approach was adopted, involving ten pre-university students enrolled in the Malaysian Higher School Certificate (STPM) Semester Two History course. The study was conducted at the Sixth Form Centre of Sekolah Menengah Kebangsaan Putatan, Penampang, Sabah. Data were collected through semi-structured interviews, classroom observations, and document analysis. The findings reveal that History teachers employed student-centred approaches by integrating various instructional strategies, including the use of Information and Communication Technology (ICT), group presentations, mind mapping, and the application of oral history methods in coursework activities. In addition, well-organised classroom management and teachers' instructional competence were identified as key supporting factors that contributed to the smooth and effective conduct of the teaching and learning process. Overall, the findings indicate that the combination of diverse student-centred strategies and effective classroom management enhances students' interest and active engagement in learning History at the preuniversity level.